Research methods in accounting - Smith, Malcolm (SAGE, 2011)
"This updated and expanded Second Edition of Research Methods in Accounting continues to provide a practical and accessible overview of the conduct of applied research studies in accounting. New to the Second Edition: expanded coverage of the areas of 'Theory' and 'Statistical Testing' to incorporate new developments; more in-depth detail on theory and associated applications, derived from behavioral, psychological, and qualitative disciplines; expanded chapter in qualitative research to reflect the movement in qualitative methodologies; treatment of the practical issues associated with the application of structural equation modeling in quantitative research; revised chapter on fieldwork to give a more considered view of qualitative research in all its alternative forms Retaining its focus on the role of theory in research, the new edition brings together the latest developments in research methods to provide candidates for PhD, DBA, Masters by research degrees in Accounting, and Master's research projects with up-to-date insights into the field of accounting and management research methods."